Estimation of the Extent of Cervical Cancer Using Multiparametric Magnetic Resonance Imaging - Е. V. Tarachkova; E. V. Nikolaev; М. A. Shorikov; V. О. Panov; I. Е. Tyurin (Вестник рентгенологии и радиологии)
Objective. To increase the efficiency of diagnosis and estimation of the local extent of a tumor process in cervical cancer (CC) using all modalities of multiparametric magnetic resonance imaging (mpMRI).Subjects and methods. Examinations were made in 31 patients (mean age 45±11 years) with histologically verified minimally invasive CC, who underwent surgical treatment. The investigators used the following modalities: T2 weighted imaging (T2WI); T2WI with fat signal suppression; diffusion-weighted image (DWI) with apparent diffusion coefficient (ADC) mapping; T1WI with dynamic contrast-enhanced MRI (DCE-MRI).Results. The measured distances significantly differed from the true ones obtained from the morphological findings (p<0.05). With allowance made for the built linear regression models, the investigators generated correction formulas. The best modality of MRI in establishing the presence of parametrial invasion in CC and in measuring the actual depth of invasion was T1WI with DCE-MRI (using the images obtained 100–125 seconds after MRI contrast medium administration); the slightly worse modality was DWI with ADC mapping (with a specificity of 91%, the sensitivities of DCE-MRI and DWI with ADC mapping were 95% and 90%, respectively), and T2WI with and without fat signal suppression.Conclusion. Quantitative analysis of the extent of CC in the parametrium according to the results of complex mpMRI seems to be a possible and highly accurate method.